The HYPER-MUCHFUSS project-the constant high-velocity population - Tillich, A.; Geier, Stephan; Heber, Ulrich; Hirsch, H.; Maxted, P. F. L.; Marsh, T.; Gaensicke, Boris T; Napiwotzki, R.; Otensen, R.; Scholz, R-D (Astrophysics and Space Science, 2010)
The HYPER-MUCHFUSS (HYPER-velocity stars or Massive Unseen Companions of Hot Faint Underluminous Stars from SDSS) project targets a population of high-velocity subluminous B stars to discover either close binaries with massive unseen companions or hyper-velocity stars. We re-observed high-velocity subdwarf selected candidates from the SDSS spectroscopic Data Release 6. Starting in 2007 we used several instruments and have now reached a completion level of 33% (from 265 targets), whereas we found at least 16 close binaries. Here we present results for two of our 39 hyper-velocity star candidates. From the available Digitized Sky Surveys photographic plates we measured a significant proper motion for 14 stars. Combining this information with a detailed spectroscopic analysis allows for the first time a complete determination of the 3D-trajectories for a high-velocity sample. We present our preliminary results for the two subdwarfs J1644+4523 and J1211+1437. Assuming the Standard Allen and Santillan (Rev. Mex. Astron. Astrofis. 22:255, 1991) potential the first one is bound and originates in the central region of the Galaxy. The subdwarf B star J1211+1437 is possibly unbound and seems to originate in the Galactic rim. We also performed numerical kinematical experiments with increased dark matter halo mass. and found that the origin of J1644+4523 in the central region is not changed but the time-of-flight is drastically shortened. J1211+1437 would be bound and probably belongs to population II.
Keywords: Kinematics; Individual; Atmospheres; Line profiles